Meat Consumption Patterns in Hawassa City, Southern Ethiopia - Lijalem, Tsegay; Beyan, Mohammed; Banerjee, Sandip (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
The study was conducted to study the consumption pattern of meat consumed (cattle, sheep and goat) at Hawassa city, Southern Ethiopia. Multistage random sampling procedure was used in the study area. Accordingly, a total of 697 households were selected. The collected data was analyzed by using descriptive statistics. Majority (95.1%) of the respondents consumed meat, the results also indicated that most of them consume meat once a month (26.8%) followed by consumption at a weekly basis (25.1%). Among the meat being consumed, beef was the most popular one and was mostly consumed on a weekly basis (23.7%) this was followed by chevon and mutton, which was mostly consumed once a month (13.9 % ,11.8%) respectively) by the respondents. The reason for preference of beef may be multifold with the higher availability (numbers of butcheries/ restaurants sold beef) and lower price of beef when compared to the other two meat types. The other reason preferred beef over mutton and chevon could be the culinary preference was towards beef related dishes which have led to higher consumption at home and eateries. The results showed that consumption of meat was highest during the festivals and holidays (89.1%), followed by times of social obligations (79.2%). Most of the respondents obtained meat through  purchasing from butchers (92.7%) or, through sharing of  slaughtered animals between friends/relatives (34.3%), by slaughtering un fattened animals, purchased directly from the market(individually(23.2%). It was concluded that in the study area, consumption status of meat was very low, only 3.2%, 5.6% and 25% of households were consumed meat (either beef or chevon or mutton) every day, twice/weekly, weekly respectively. Therefore, any development and improvement strategies of livestock production should be introduced so as to secure meat requirement of the community in the study area, Ethiopia.